Exotic seafood at a reasonable price - Mumbai Archive Project Team (Jio Institute, 2024)
A big draw of the festival is the chance to savour exotic seafood at reasonable prices. Crabs (kekda), oysters, lobsters, squid, and raw fish eggs (gaboli) are in high demand during festival days.